Breast Metastasis From Rectal Signet-Ring Cell Carcinoma: A Case Report and Review of Literature - Dai, Yuran; Jin, Yudi; Lan, Ailin; Ding, Nan; Jiang, Linshan; Liu, Shengchun (Frontiers in Oncology, 2022)
Background: Metastatic rectal cancer (mRC) to the breast is an extremely rare clinical situation. There are few reported cases in the domestic or foreign literature. The clinicopathological characteristics along with the diagnostic and therapeutic strategies of such cases remain relatively unclear. Here, we would like to provide our comprehensive insights into this rare entity. Methods: We present a case that till now is the first reported breast metastasis from rectal cancer pathologically diagnosed as a signet ring cell carcinoma and review the current literature on this rare event. The detailed clinical data, histopathology, management, and follow-up aspects were gathered for analysis. Results: A total of 15 cases were collected including the current case. Breast metastases from rectal cancer present at an average age of 47.7 years and appear with an average interval of 28.4 months following primary tumor diagnoses. 8/15 and 5/15 of cases are pathologically diagnosed as adenocarcinomas and mucinous adenocarcinomas, respectively. Most cases (11/15) are accompanied by extramammary metastases. About half of the breast metastases (7/15) were to the left. In all cases, the main complaints were palpable mass. The average maximum diameter of the metastatic mass is 2.7cm. The majority (8/12) of cases with accessible therapy information exclude the option of local surgery. Conclusion: Previous cancer history and accurate immunohistochemistry data play critical roles to distinguish mammary metastasis from a primary neoplasm of the breast. Mastectomy and molecular-targeted drugs should be considered with priority if systemic condition supports.